Difference in C3–C4 metabolism underlies tradeoff between growth rate and biomass yield in Methylobacterium extorquens AM1. Issue 1 (December 2016) - Fu, Yanfen; Beck, David; Lidstrom, Mary
Abstract Background Two variants ofMethylobacterium extorquens AM1 demonstrated a trade-off between growth rate and biomass yield. In addition, growth rate and biomass yield were also affected by supplementation of growth medium with different amounts of cobalt. The metabolism changes relating to these growth phenomena as well as the trade-off were investigated in this study.13 C metabolic flux analysis was used to generate a detailed central carbon metabolic flux map with both absolute and normalized flux values. Results The major differences between the two variants occurred at the formate node as well as within C3–C4 inter-conversion pathways. Higher relative fluxes through formyltetrahydrofolate ligase, phosphoenolpyruvate carboxylase, and malic enzyme led to higher biomass yield, while higher relative fluxes through pyruvate kinase and pyruvate dehydrogenase led to higher growth rate. These results were then tested by phenotypic studies on three mutants (nullpyk, nullpck mutant and nulldme mutant) in both variants, which agreed with the model prediction. Conclusions In this study, 13 C metabolic flux analysis for two strain variants ofM. extorquens AM1 successfully identified metabolic pathways contributing to the trade-off between cell growth and biomass yield. Phenotypic analysis of mutants deficient in corresponding genes supported the conclusion that C3–C4 inter-conversion strategies were the major response to the trade-off.